Characterization of genomic variations in SNPs of PE_PGRS genes reveals deletions and insertions in extensively drug resistant (XDR) M. tuberculosis strains from Pakistan. (March 2015) - Kanji, Akbar; Hasan, Zahra; Ali, Asho; McNerney, Ruth; Mallard, Kim; Coll, Francesc; Hill-Cawthorne, Grant; Pain, Arnab; Nair, Mridul; Clark, Taane G.; Zaver, Ambreen; Jafri, Sana; et al.
Abstract: Background: Mycobacterium tuberculosis (MTB) PE_PGRS genes belong to the PE multi-gene family. Although the function of the members of the PE_PGRS multi-gene family is not yet known, it is hypothesized that the PE_PGRS genes may be associated with genetic variability. Material and methods: Whole genome sequencing analysis was performed on ( n  = 37) extensively drug resistant (XDR) MTB strains from Pakistan which included Central Asian ( n  = 23), East African Indian ( n  = 2), X3 ( n  = 1), T group ( n  = 3) and Orphan ( n  = 8) MTB strains. Results: By analyzing 42 PE_PGRS genes, 111 SNPs were identified, of which 13 were non-synonymous SNPs (nsSNPs). The nsSNPs identified in the PE_PGRS genes were as follows: 6, 9, 10 and 55 present in each of the CAS, EAI, Orphan, T1 and X3 XDR MTB strains studied. Deletions in PE_PGRS genes: 19, 21 and 23 were observed in 7 (35.0%) CAS1 and 3 (37.5%) in Orphan XDR MTB strains, while deletions in the PE_PGRS genes: 49 and 50 were observed in 36 (95.0%) CAS1 and all CAS, CAS2 and Orphan XDR MTB strains. An insertion in PE_PGRS6 gene was observed in all CAS, EAI3 and Orphan, while insertions in the PE_PGRS genes 19 and 33 were observed in 19 (95%) CAS1 and all CAS, CAS2, EAI3 and Orphan XDR MTB strains. Conclusion: Genetic diversity in PE_PGRS genes contributes to antigenic variability and may result in increased immunogenicity of strains. This is the first study identifying variations in nsSNPs, Insertions and Deletions in the PE_PGRS genes of XDR-TB strains from Pakistan. It highlights common genetic variations which may contribute to persistence.